2023
DOI: 10.1021/acsnano.3c05635
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Cancer Vaccines: Construction and Boosting Strategies

Xiaoqing Liu,
Pei Huang,
Rusen Yang
et al.

Abstract: In late 2020, the U.S. Food and Drug Administration (FDA) approved a lipid-based mRNA vaccine for the prevention of COVID-19, which has pushed this field to be more closely studied and motivated researchers to delve deeper into mRNA therapeutics. To date, the research on mRNA cancer vaccines has been developed rapidly, and substantial hopeful therapeutic results have been achieved against various solid tumors in clinical trials. In this review, we first introduce three main components of mRNA cancer vaccines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 234 publications
0
6
0
Order By: Relevance
“…Many studies have shown that moderate immune stimulation is beneficial to improve the effectiveness of the vaccine. We then employed the P6/mOVA nanovaccine to investigate the influence of the polymeric nanocarrier on DC maturation and activation. According to Figure a, the group with only P6 had a certain effect on promoting the maturation of DC2.4 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that moderate immune stimulation is beneficial to improve the effectiveness of the vaccine. We then employed the P6/mOVA nanovaccine to investigate the influence of the polymeric nanocarrier on DC maturation and activation. According to Figure a, the group with only P6 had a certain effect on promoting the maturation of DC2.4 cells.…”
Section: Resultsmentioning
confidence: 99%
“…mRNA vaccines can encode almost any protein and facilitate post-translational modifications within cells. This capability reduces immunogenicity while ensuring the functionality of protein products, leading to significant breakthroughs in treating various diseases [ 5 7 ]. (2) Efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…According to the traditional view, an mRNA vaccine comprises three components: mRNA sequence containing antigen, DDS or vector, and adjuvant. Adjuvant is an immunostimulant that is added in addition to a vector or DDS to non-specifically enhance the body’s specific immune response to the antigen [ 7 ]. Conversely, some scholars argue that adjuvants should include DDS in addition to traditional adjuvants [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both the reactivation and ex novo generation of T cell-driven antitumor activity are the ultimate goals of several anticancer immunotherapies, including those based on immune checkpoint inhibitors (ICIs) [ 2 ], chimeric antigen receptor (CAR) T cells [ 3 ], and mRNA-based vaccines [ 4 ]. At present, ICIs and CAR-T cells are in use in clinics.…”
Section: Introductionmentioning
confidence: 99%